An analysis of proportional reasoning ability of junior high school students - Fitria Mardika; Ali Mahmudi (Jurnal Riset Pendidikan Matematika, 2021)
This study aims to describe proportional reasoning skills and students’ difficulties in solving proportional reasoning problems. The population of this research was 3480 seventh-grade students of state junior high schools in the Yogyakarta region. The samples were 158 students chosen using proportionate stratified random sampling that represent four categories of school (very high, high, medium, low) based on the average scores of the national examination in mathematics in 2016. Data were collected through essay tests and interviews. Data were analyzed quantitatively and qualitatively. The result showed that the students in very high and high category schools had moderate proportional reasoning ability. Students in medium and low category schools had low proportional reasoning ability. Students’ difficulties in solving proportional reasoning problems vary based on the type of the problem, such as the difficulty in finding the multiplicative relationship contained in the problem, the difficulty in understanding the value of inverse proportion, and the difficulty in explaining the obtained solution of the problems.